PERANCANGAN SISTEM INFORMASI DONASI BERBASIS ANDROID (STUDI KASUS YAYASAN AS-SUNNAH JAMBI): System, Information, Android - Ikhsan, Muhammad; Adhiatma, Novri; Kurniady , Dedi (JURNAL AKADEMIKA, 2018)
The As-Sunnah Foundation Jambi is a legal entity with social, religious and humanitarian purposes and objectives, established on May 15, 2012 and located at Jl. Country Taruma No.66 RT.012 Ex. Tanjung Pinang Kec. East Jambi. The As-Sunnah Foundation of Jambi conducts many social, religious and humanitarian activities such as holding Islamic boarding schools, madrassas, and study places, providing assistance to disaster victims, receiving and distributing infaq or sodaqoh as well as performing religious ceremonies. The purpose of this study is to analyze the existing system, in order to solve the problems faced by the As-Sunnah Foundation Jambi by designing the application of Islamic information system based on android. The stages to be done in solving the problems discussed are, identifying, searching the theories of data collection with observation and interview methods, analyzing to find solutions to the problems faced by As-Sunnah Foundation Jambi, developing system using Data model Flow Diagram (DFD) and create reports. The purpose of this study is to create an Islamic information system that can assist in the delivery of Islamic information conducted As-Sunnah Foundation Jambi.